Environmental, Ecological and Human Health Risk Assessment of Heavy Metals in Sediments at Samsun-Tekkekoy, North of Turkey - Simsek, Arife; Ozkoc, Hulya Boke; Bakan, Gulfem (Springer Heidelberg, 2022)
A detailed study was conducted in order to evaluate the effects of heavy metal pollution in the sediments in terms of environmental, ecological, and human health. Sediment samples were collected from 5 different points in two seasons, namely summer (August 2017) and winter (December 2017), to determine the distribution of heavy metals, potential pollutants, and toxic and ecological risks in the river sediments in Samsun-Tekkekoy district located in the Mid-Black Sea Region of Turkey and to evaluate the human health risk. The distribution of heavy metals at the sampling points was Fe>Al>Mn>Zn>Cu>Cr>Ni>Pb>Cd based on their averages. According to the toxic risk index (TRI) results, sampling point OIZ (Organized Industrial Zone) Channel (T3) was also found to have a moderate risk, and it was determined that the highest contribution was from Cu>Ni>Cd>Cr, respectively. Potential ecological risk index (PERI) results revealed a low risk except for Cd metal at all sampling points. While the sediment enrichment factor (EF) did not show much metallization at many points, the highest enrichment was observed in Cd, Cu, and Zn metals at sampling point T3. According to the geoaccumulation index (I-geo) and contamination factor (C-F), sampling point T3 showed contamination with Cd, Cu, Cr, and Zn. Evaluation of human health risk showed that the hazard index (HI) results of carcinogenic and non-carcinogenic risks were higher among children than adults. The total lifetime cancer risks (TLCR) of heavy metals were within the limits determined by USEPA. However, the risk was ranked as Cr>Cd>Pb. Sediment quality guidelines (SQGs) and pollution index results showed that heavy metal contamination was due to anthropogenic and industrial activities since the region was an industrial zone. It was determined that heavy metals posed ecological risks and that the Samsun-Tekkekoy region was moderately and significantly contaminated.
Ozkoç, Hülya Saide/0000-0002-8775-837X; Siek, Arife/0000-0002-7177-1764;
Keywords: Ecological Risk; Heavy Metal; Human Health Risk; Risk Assessment; Sediment; Turkey